Mineral lick use by a community of large herbivores in northern Iran. Issue 1 (18th January 2023) - Salmanpour, Farid; Shakoori, Zahra; Kia, Mehdi; Eshaghi, Rahman; Ghaderi, Mehdi; Ghomi, Saied; Kaveh, Reza; Rabie, Kuros; Kiabi, Bahram H.; Farhadinia, Mohammad S.
Abstract: Natural mineral licks are ecologically valuable resources to meet the physiological needs of herbivores, particularly in temperate forests. Importantly, licking sites can harbor high anthropogenic risk for conservation‐dependent herbivores through higher chance of pathogen spillover from livestock and increased levels of poaching risks. However, to the best of our knowledge, there is no information on the mineral lick use in temperate forests of west Asia and the Caucasus where a few threatened deer species exist. We monitored four naturally occurring mineral licks in Central Alborz Protected Area, northern Iran during May–July 2019 using camera traps and analyzed the mineral content of the licking sites. A total of 53 independent mineral lick visits were obtained from only three species of herbivores, i.e., Caspian red deer ( Cervus elaphus maral ; n = 21), roe deer ( Capreolus capreolus ; n = 26), and wild pig ( Sus scrofa ; n = 6). The sex ratio of visiting Caspian red deer was highly skewed toward females (3M:18F), whereas it was more balanced in visiting roe deer (11M:15F). The species‐level distribution of visits corresponded to diurnal and cathemeral for Caspian red deer and for roe deer, respectively, without any evidence of different activity curves. There was a negative nonlinear relationship between the ambient temperature and the visitation rate. Our findings showed that mineral licks are important habitat features for these large herbivores and need to be included in spatial mapping and habitat protection measures. Abstract : Natural mineral licks are ecologically valuable resources to meet the physiological needs of herbivores, particularly in temperate forests. Importantly, licking sites tend to have higher anthropogenic risk on conservation‐dependent herbivores through higher chance of pathogen transmission from livestock and higher levels of poaching risks. However, to the best of our knowledge, there is no information on the mineral lick use in temperate forests of west Asia and the Caucasus where a few threatened deer species exist.